A previously uncultured, paper mill Propionibacterium is able to degrade O-aryl alkyl ethers and various aromatic hydrocarbons - Thorenoor, Nithyananda; Kim, Yong-Hak; Lee, Cheolju; Yu, Myeong-Hee; Engesser, Karl-Heinrich (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
A previously uncultured Propionibacterium was isolated from a highly diluted sample (10(-6) mL) of activated sludge of paper mill effluent. The isolate MOB600 was able to grow on anisole, phenetole, benzene, toluene, phenol, styrene and biphenyl, although it used only limited carbon sources in the minimal media. The partial DNA sequence of 16S ribosomal RNA gene was 93% identical to Luteococcus peritoni CCUG38120 as the closest neighborhood in the family Propionibacteriaceae. Strain MOB600 produced 2-methoxyphenol and 2-ethoxyphenol seemingly in an unproductive pathway from the degradation of anisole and phenetole, respectively. It had a substrate preference to favor 3-alkoxyphenols over 2-alkoxyphenols. Formation of 3-hydroxylated O-aryl alkyl ether was substantially proved by the nearly 1:1 biotransformation of substrate-analogous 1,2-methylenedioxybenzene to 3,4-methylenedioxyphenol (sesamol) showing end-product inhibition. The strain converted 2-/3-methoxyphenols to 3-methoxycatechol. The extradiol ring fission of 3-methoxycatechol appeared to take place in the production of a yellow-colored 2-hydroxymuconate derivative, thereby being able to release methanol spontaneously. High specificity polymerase chain reaction screening for bacterial dioxygenases revealed that the genomic DNA encoded at least three ring-hydroxylating dioxygenase large subunits. Being consistent with substrate availability for this strain, the obtained sequences were closely related to large subunits of an isopropylbenzene 2,3-dioxygenase, a benzene 1,2-dioxygenase, a biphenyl 2,3-dioxygenase, a benzoate 1,2-dioxygenase and a putative dioxygenase in Rhodococcus strains. Our results demonstrate that strain MOB600 may play a major role in the degradation of lignin-like O-aryl alkyl ethers and various aromatic hydrocarbon pollutants in activated sludge of paper mill effluent. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: ACTIVATED-SLUDGE; PSEUDOMONAS; PEROXIDASE; COMMUNITY; STRAIN; GENES; SOILS; ACID